Incidence, outcomes and management of spontaneous haemoperitoneum in pregnancy: a UK population-based study [version 2; peer review: 2 approved] - Ruth Tunn; Rema Ramakrishnan; Marian Knight; Hilde Marie Engjom (NIHR Open Research, 2025)
Background Spontaneous haemoperitoneum in pregnancy (SHiP) is the occurrence during pregnancy of sudden intra-abdominal haemorrhage unrelated to extrauterine pregnancy, trauma or uterine rupture. SHiP is uncommon but is associated with preterm birth, high perinatal mortality and, more rarely, maternal mortality. We investigated the incidence of SHiP in the UK and its diagnosis, management and outcomes. Methods This two-year, prospective surveillance study used the UK Obstetric Surveillance System to collect anonymous data on all women who gave birth in a UK consultant-led maternity unit in 2016 and 2017 and who experienced SHiP. Results We confirmed 20 cases of SHiP, giving an estimated incidence of 1.3 cases per 100,000 maternities, or 1 per 75,614 maternities. The median gestational age at diagnosis was 35.7 weeks (IQR 29.9–38.4 weeks). A minority of affected women were receiving anticoagulant agents for prophylaxis (2/20) or treatment (4/20). The most common initial suspected diagnosis was placental abruption (7/20), followed by intra-abdominal bleeding, uterine rupture, or infection. SHiP was diagnosed using ultrasound in four women, using CT in five, and solely at surgery in 14. Aneurysms (4/20) and organ rupture or haematoma (5/20) were the most common bleeding source, and the condition was most commonly diagnosed and treated by laparotomy (11/20). Perinatal morbidity and mortality were high, with 16% of infants stillborn, an over 80% admission rate to the neonatal unit among the 16 live-born infants, major complications in a third of these infants, and one neonatal death. Maternal morbidity was also high, with 60% of women admitted to the intensive care unit, over half of whom experienced major morbidity, and one maternal death. Conclusions SHiP is rare in the UK but when it occurs, it can be associated with major maternal morbidity and mortality, and perinatal outcomes are poor. International comparisons are complicated by differing definitions of SHiP.